Interpol Red Notices as Surrogate Tools of Political Persecution: Normative Failure and Reform - Ignasius Justin Devrata; Joko Setiyono (Rechtsnormen: Journal of Law, 2026)
Background. INTERPOL Red Notices are designed to facilitate international police cooperation by assisting member countries in locating and provisionally arresting wanted persons pending extradition or similar legal proceedings. However, in practice, Red Notices may produce coercive effects despite their non-binding character, particularly when used by authoritarian regimes to pursue political opponents, journalists, human rights defenders, refugees, and exiled critics across jurisdictions. Purpose. This study aims to analyze the normative failure of existing protection mechanisms, particularly Article 3 of the INTERPOL Constitution and the Commission for the Control of INTERPOL’s Files (CCF), in preventing the misuse of Red Notices as surrogate tools of political persecution, and to formulate a reconstructed normative oversight framework. Method. This research employs doctrinal legal research with a prescriptive-analytical specification, using statutory, conceptual, case-based, comparative, and historical approaches. The legal materials consist of INTERPOL legal instruments, CCF-related documents, international human rights norms, selected cases, scholarly literature, and comparative legal materials. Results. The study finds that the normative failure arises from the abstract formulation of Article 3, formalistic assessment of ordinary criminal charges, reactive nature of CCF remedies, limited procedural transparency, reliance on information supplied by requesting states, and fragmented domestic implementation of Red Notices. Conclusion. The oversight of INTERPOL Red Notices should be reconstructed through a preventive, contextual, and rights-based framework, including a contextual political-motivation test, heightened scrutiny for vulnerable political targets, rebuttable presumptions in refugee or asylum-related cases, burden-shifting to requesting states, stronger interim measures, and greater procedural transparency.